"A matter of time": Evidence-making temporalities of vaccine development in the COVID-19 media landscape. (February 2022) - Harrison, Mia; Lancaster, Kari; Rhodes, Tim
This article investigates how evidence of the safety and efficacy of COVID-19 vaccines is enacted in news media via a focus on the temporality of vaccine development. We argue that time constitutes a crucial object of and mechanism for knowledge production in such media and investigate how time comes to matter in vaccine evidence-making communication practices. In science communication on vaccine development, the vaccine object (along with the practices through which it is produced) undergoes a material-discursive shift from an imagined "rushed" product to being many years in the making and uninhibited by unnecessarily lengthy processes. In both these enactments of vaccine development, time itself is constituted as evidence of vaccine efficacy and safety. This article traces how time (performed as both calendar time and as a series of relational events) is materialized as an affective and epistemic object of evidence within public science communication by analyzing the material-discursive techniques through which temporality is enacted within news media focused on the timeline of COVID-19 vaccine development. We contend that time (as evidence) is remade through these techniques as an ontopolitical concern within the COVID-19 vaccine assemblage. We furthermore argue that science communication itself is an important actor in the hinterland of public health practices with performative effects and vital evidence-making capacities.